Endovascular Treatment Increases but Gamma Knife Radiosurgery Decreases Angiogenic Activity of Arteriovenous Malformations: An in Vivo Experimental Study Using a Rat Cornea Model - (:unkn) unknown (OXFORD UNIV PRESS INC, 2010)
OBJECTIVE: To compare the angiogenic potentials of embolized, gamma knife-treated or untreated cerebral arteriovenous malformations (AVMs), using a rat cornea angiogenesis model. METHODS: Tissue samples from cerebral AVM patients who were either untreated or had previously been treated with embolization or gamma knife radiosurgery and who had undergone operations for hemorrhage at the Neurosurgery Department or the Neurological Sciences Institute of Marmara University were used. For the macroscopic evaluation of angiogenesis, tissue samples were inoculated in a micropocket created on the rat eye, and the level of angiogenic activity was graded macroscopically for 15 days, with glioblastoma multiforme and normal brain artery tissues serving as positive and negative controls, respectively. For the other part of the experiment, eyes of another set of rats were inoculated with the study samples only using the same cornea angiogenesis model, in which microvessel count and vascular endothelial growth factor assessment was done at days 3, 7, 11, and 15. RESULTS: Based on our macroscopic findings in the cornea angiogenesis model, embolized AVMs exhibited the highest angiogenic activity, followed by untreated AVMs and gamma knife-treated AVMs. Evaluations of vascular endothelial growth factor expression and microvessel counts showed a similar relation among the 3 tissue groups with regard to the level of angiogenic activity, supporting the results of macroscopic examinations. CONCLUSION:This study, for the first time, provides experimental semiquantitative data to compare the angiogenic potentials of embolized and gamma knife-treated AVM tissues. Embolization may increase angiogenic activity, and gamma knife radiosurgery may decrease it when compared with activity in previously untreated AVMs. These data can be useful to understand why recurrence of AVMs after angiographically demonstrated endovascular occlusion is common but after gamma knife occlusion is rare.
Keywords: Angiogenesis; Arteriovenous malformation; Cornea angiogenesis model; Embolization; Endovascular treatment; Gamma knife radiosurgery; ENDOTHELIAL GROWTH-FACTOR; HUMAN CEREBROVASCULAR MALFORMATIONS; GENE MICROARRAY ANALYSIS; CENTRAL-NERVOUS-SYSTEM; STRUCTURAL PROTEINS; VASCULAR MALFORMATIONS; LINAC RADIOSURGERY; SURGICAL EXCISION; EXPRESSION; RECURRENCE